A CONSTRUCTIVE HEURISTIC FOR THE CONTAINER RELOCATION PROBLEM - Wu, Kun-Chih; Ting, Ching-Jung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
Container terminal faces a challenge of handling the growing number of containers to adapt the expansion of globalized economy. Reducing container relocation is an important issue in port operational aspect, because the relocation is a non-value-added movement but a time consuming and wasteful activity. In this study, a container relocation problem (CRP) is considered to apply the minimum number of relocations to retrieve all containers stored at a bay. Specifically, the unrestricted-CRP is concerned in this paper, in which not limited to the containers above the target container can be relocated. We propose a novel constructive heuristic to quickly generate a good quality solution to the container relocation problem. Benchmark of total 12500 instances from the literature is tested and compared. The computational results show that, comparing to the existing construction heuristic, our heuristic can improve 3.55% in average number of relocations.